Sains Islam dan Struktur Institusional Eropa: Pengaruh Struktur Madrasah dan Kurikulum Arab terhadap Universitas Paris dan Oxford pada Abad ke-13 - Yolan Azhari; Ridho Magrizani; Muhammad Syamsul Munir (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
ABSTRACT Mainstream historiography regarding the origins of universities in Western Europe has long been plagued by Eurocentric biases that view these institutions as exclusive products of medieval Western Latin Christian ingenuity. This article deconstructs this narrow narrative by analyzing the structural, managerial, and curricular blueprint provided by Islamic civilization for the transformation of the University of Paris and the University of Oxford in the 13th century. Employing the Critical Historical Method integrated with Comparative Institutionalism, this study examines the structural parallelism between Islamic Madrasahs and early European corporations. The findings reveal that the assimilation of the Arab-Islamic natural philosophy corpus triggered a methodological reform from the traditional passive teaching model (lectio) into a dialectical debate method (disputation/quaestio disputata), which directly replicated the tradition of munazarah or jadal in Madrasahs. Furthermore, a sociological shift occurred from the personal authority of the teacher in the ijazah system toward institutional-corporate authority in the form of licentia docendi, acting as an instrument of social exclusion. Finally, the managerial blueprint of madrasahs based on Islamic endowment law (Waqf) inspired financial independence and trust law in Western statutes, while the spatial model of the Khan complex adjacent to mosques was architecturally replicated as the foundation of the Collegiate System. This study demonstrates a profound transfer of social technology from Islam to the West. Keywords: Islamic Science, Madrasah, 13th Century Universities, Licentia Docendi, Collegiate System, Comparative Institutionalism. ABSTRAK Historiografi arus utama mengenai asal-usul universitas di Eropa Barat telah lama dihinggapi oleh bias Eurosentris yang memandang institusi-institusi ini sebagai produk eksklusif dari kecerdasan Kristen Latin Barat abad pertengahan. Artikel ini mendekonstruksi narasi sempit tersebut dengan menganalisis cetak biru struktural, manajerial, dan kurikuler yang disediakan oleh peradaban Islam bagi transformasi Universitas Paris dan Universitas Oxford pada abad ke-13. Menggunakan Metode Sejarah Kritis yang diintegrasikan dengan Institusionalisme Komparatif, studi ini menguji paralelisme struktural antara Madrasah Islam dan korporasi awal Eropa. Hasil penelitian menunjukkan bahwa asimilasi korpus filsafat alam Arab-Islam memicu reformasi metodologis dari model pengajaran pasif tradisional (lectio) menjadi metode debat dialektis (disputation/quaestio disputata), yang secara langsung mereplikasi tradisi munazarah atau jadal di Madrasah. Selain itu, terjadi pergeseran sosiologis dari otoritas personal guru dalam sistem ijazah menuju otoritas institusional-korporasi dalam bentuk licentia docendi, yang berfungsi sebagai instrumen eksklusi sosial. Terakhir, cetak biru manajerial madrasah berdasarkan hukum wakaf Islam menginspirasi independensi finansial dan hukum kepercayaan (trust law) dalam statuta Barat, sementara model spasial kompleks Khan di dekat masjid direplikasi secara arsitektural sebagai fondasi Sistem Kolegiat. Studi ini membuktikan adanya transfer teknologi sosial yang mendalam dari dunia Islam ke dunia Barat.